TEACHERS’ AND STUDENTS’ PERCEPTIONS OF USING ISLAMIC TEXTS IN ENGLISH READING INSTRUCTION - Oktariyani; Herlina, Ninin; Said, Ratna; Im, Hyunbim; Semyanov, Larra (INTIHA: Islamic Education Journal, 2026)
This study examines teachers’ and students’ perceptions of integrating Islamic texts into English reading instruction at an Islamic high school in Tangerang, Indonesia. Although religious texts have the potential to support literacy development and character education, current English learning materials lack such integration. To address this gap, the study explores how educators and learners perceive Islamic texts and identifies the benefits and challenges of incorporating them into English reading classes. Using a descriptive qualitative approach, data were collected through in-depth interviews with three English teachers and three students, open-ended questionnaires administered to thirty students, four classroom observations, and document analyses of syllabi and lesson plans. The findings show that both teachers and students respond positively to using Islamic texts: teachers regard them as effective tools for promoting moral values and enhancing reading skills, while students report increased engagement, motivation, and a stronger connection to the content. However, challenges include sourcing level-appropriate materials, managing linguistic complexity, and ensuring inclusivity in diverse classroom contexts. The study recommends careful material selection, collaboration between English and Islamic education teachers, and the use of varied multimodal resources aligned with the CEFR to integrate language instruction and character development effectively.